Effect of addition of MTES on the structure of siloxane-PPG nanocomposites - Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Lafontaine, E.; Judeinstein, P.; Craievich, A. F. (Springer, 2000)
Hybrid transparent and flexible siloxane-polypropyleneglycol (PPG) materials with covalent bonds between the inorganic (siloxane) and organic (polymeric) phases were prepared by sol-gel process. In order to improve the quality of the mechanical properties of these materials, different amounts of methyltriethoxysilane (MTES) were added to the initial sol. The effect of MTES addition on the structure of the composites was studied by Small-Angle X-Ray Scattering (SAXS) and Si-29 Nuclear Magnetic Resonance (Si-29 NMR). In absence of MTES, SAXS spectra exhibit a peak that is assigned to spatial correlation due to short range order between the siloxane clusters embedded in the polymeric phase. The experimental results indicate that, for low MTES concentrations ([MTES]/[O] less than or equal to 0.8, O: ether-type oxygen of PPG), the silicon species resulting from hydrolysis and condensation of MTES fill the open spaces between polymeric chains, interacting with the ether-type oxygens. For larger MTES content ([MTES]/[O] greater than or equal to 0.8), the number of free ether-type oxygen sites avalaible for reaction with such silicon species is not large enough. Consequently, a fraction of silicon species resulting from MTES addition graft to siloxane clusters formed by hydrolysis and condensation of the hybrid precursor. For all MTES concentrations the condensation degree of the siloxane phase, determined from Si-29 NMR spectroscopy, is high (> 69%), as expected under neutral pH synthesis conditions.
Keywords: hybrid materials; xerogels structure; small-angle x-ray scattering; nuclear magnetic resonance; nanostructures